Chaperoned amyloid proteins for immune manipulation: α‐Synuclein/Hsp70 shifts immunity toward a modulatory phenotype. Issue 4 (5th December 2014) - Labrador‐Garrido, Adahir; Cejudo‐Guillén, Marta; Klippstein, Rebecca; De Genst, Erwin J.; Tomas‐Gallardo, Laura; Leal, María M.; Villadiego, Javier; Toledo‐Aral, Juan J.; Dobson, Christopher M.; Pozo, David; Roodveldt, Cintia
Abstract α‐Synuclein (αSyn) is a 140‐residue amyloid‐forming protein whose aggregation is linked to Parkinson's disease (PD). It has also been found to play a critical role in the immune imbalance that accompanies disease progression, a characteristic that has prompted the search for an effective αSyn‐based immunotherapy. In this study, we have simultaneously exploited two important features of certain heat‐shock proteins (HSPs): their classical "chaperone" activities and their recently discovered and diverse "immunoactive" properties. In particular, we have explored the immune response elicited by immunization of C57BL/6 mice with an αSyn/Hsp70 protein combination in the absence of added adjuvant. Our results show differential effects for mice immunized with the αSyn/Hsp70 complex, including a restrained αSyn‐specific (IgM and IgG) humoral response as well as minimized alterations in the Treg (CD4+CD25+Foxp3+) and Teff (CD4+Foxp3−) cell populations, as opposed to significant changes in mice immunized with αSyn and Hsp70 alone. Furthermore, in vitro‐stimulated splenocytes from immunized mice showed the lowest relative response against αSyn challenge for the "αSyn/Hsp70" experimental group as measured by IFN‐γ and IL‐17 secretion, and higher IL‐10 levels when stimulated with LPS. Finally, serum levels of Th1‐cytokine IFN‐γ and immunomodulatory IL‐10 indicated a unique shift toward an immunomodulatory/immunoprotective phenotype in mice immunized with the αSyn/Hsp70 complex. Overall, we propose the use of functional "HSP‐chaperoned amyloid/aggregating proteins" generated with appropriate HSP‐substrate protein combinations, such as the αSyn/Hsp70 complex, as a novel strategy for immune‐based intervention against synucleinopathies and other amyloid or "misfolding" neurodegenerative disorders.